Axially loaded of cold-formed steel columns with opening - Nurul Atikah, Zulkipli (2017)
This paper presents study the buckling behavior of cold-formed single C-section with opening. Cold-formed steel is the common term for products made by rolling or pressing steel into semi-finished or finished goods at relatively low temperatures. The method used for this experiment are compression test. The column specimens were compressed between bearing plate with flat ends. 7 number of specimens with height of 600 mm with one without opening and the other 6 with openings had been used in this experiment. The shape of openings used are circle and the size are keep constant that is 25 mm diameter to ensure the consistency in the result making. The ultimate load strength of the cold-formed steel section and failure modes differs depend on the position of the openings, where the conclusions are make on the basis of the comparisons between the positions of openings. Transducers used to read the displacement of the specimen during testing where the graph had been plotted. The load – displacement graph study the movement of the flange during compression test. The distance between openings and the opening distance from the support did make a difference to the results but the difference did not varies much due to the smaller distance between openings. Local buckling and distortional buckling can be seen at the specimen. Local buckling only happen at the specimen that did not has openings while for specimen that have openings, distortional buckling occurred where the flanged distort outward or inward can be seen.